Land Dispute Resolution Regarding The Sale And Purchase Of Customary Land Based On Rejang Customary Law In Kepahiang Regency From The Perspective Of The Basic Agrarian Law (UUPA) - Yusuf, Muhammad Mulyadi; Jaya, Dwi Putra; Aprianto, Sandi (JURNAL HUKUM SEHASEN, 2026)
Land is a gift from God Almighty in the form of a natural resource that is essential for humans to meet their needs, both directly for life, such as for farming or for housing, as well as for carrying out their businesses such as for trade, industry, education, and the construction of other facilities and infrastructure. The Land Dispute Law, Regulation of the Head of the Indonesian National Land Agency No. 3 of 2011, explains that a land dispute is land whose ownership is disputed by two parties who wish to claim ownership of the land. Land disputes tend to occur frequently in Indonesia and are one of the most inevitable disputes today. Such disputes can arise for various reasons, such as unclear land boundaries, conflicting ownership claims, inheritance disputes, or changes in spatial planning. To avoid such problems, it is necessary to check the ownership status of the property you are planning to purchase, whether through an intermediary or without an intermediary. Common methods include obtaining a valid land certificate document from a legal entity, as well as the authenticity of the certificate ownership.